DAMPAK PENGGUNAAN GADGET TERHADAP KETERAMPILAN BERKOMUNIKASI INTERPERSONAL SISWA SEKOLAH DASAR - Nursalim; Puaddi; Habibul Hakim; M. Anas Nazarsyah R. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of information and communication technology, particularly the use of gadgets, has had a significant impact on the interpersonal communication skills of elementary school students. This study aims to examine the impact of gadget use on students' interpersonal communication skills through a library research approach using a descriptive-analytical method. Data was obtained from various secondary sources such as relevant scientific journals, books, and dissertations, then analyzed using a thematic approach. The results of the study indicate that gadget use has both positive and negative impacts on students' interpersonal communication. Positive impacts are seen in increased digital communication skills, the courage to express opinions, and the expansion of students' social insights through access to information and virtual interactions. However, excessive gadget use tends to decrease the quality of direct interpersonal communication, such as reduced face-to-face interaction, the emergence of individualistic attitudes, and low social sensitivity. Furthermore, long-term use is also associated with decreased social skills in students. Therefore, supervision and control of gadget use by parents and teachers are necessary to maintain balance. Wise use of gadgets is expected to support the optimal development of students' interpersonal communication amidst advances in digital technology.